2012
DOI: 10.3928/01477447-20120426-17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Computer-assisted Versus Conventional Total Knee Arthroplasty

Abstract: The purpose of this study was to determine whether the use of computer-assisted surgery can improve the clinical results in total knee arthroplasty (TKA) compared with conventional methods of TKA.A literature search of PubMed (1966 to August 2011), CENTRAL (Cochrane Controlled Trials Register; issue 3, 2011), and EMBASE (1984 to August 2011) was conducted. Randomized, controlled trials detecting the clinical outcomes of TKA with or without the use of computer-assisted surgery were identified. A meta-analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…While our findings are consistent with those of numerous other authors that CAS results in a mechanical axis closer to neutral, the clinical benefit of this finding has yet to be clearly demonstrated through the use of accepted clinical evaluation tools [17][18][19][20]. Furthermore, using CAS for TKA involves recurring costs and often results in increased operative time.…”
Section: Discussionsupporting
confidence: 87%
“…While our findings are consistent with those of numerous other authors that CAS results in a mechanical axis closer to neutral, the clinical benefit of this finding has yet to be clearly demonstrated through the use of accepted clinical evaluation tools [17][18][19][20]. Furthermore, using CAS for TKA involves recurring costs and often results in increased operative time.…”
Section: Discussionsupporting
confidence: 87%
“…Also, we contacted experts in the field resulting in one more article eligible for inclusion. As a result, we included 42 SRs 12–14 36–74…”
Section: Resultsmentioning
confidence: 99%
“…Three functional outcomes were compared for TKA 14 45 60 64 67 69 71 72. Knee Society Scores: Two out of eight SRs showed that CA TKA had superior scores,14 60 while six out of eight SRs showed no difference 45 64 67 69 71 72. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC): One out of three SRs showed slightly improved scores with the CA TKA,60 while two out of three SRs showed no difference 71 72.…”
Section: Resultsmentioning
confidence: 99%
“…In CAS the cost, operating time, chances of periprosthetic fractures are very high. 3,4,5 The need to overcome these limitations led to the development of hand held navigation system. It has showed promising results for achieving accurate tibial and femoral resection and alignment as with the same degree of accuracy as with large console CAS systems, while preventing the above mentioned concern.…”
Section: Introductionmentioning
confidence: 99%
“…It has showed promising results for achieving accurate tibial and femoral resection and alignment as with the same degree of accuracy as with large console CAS systems, while preventing the above mentioned concern. 5 It also does not depend on assumptions based on the axes of the femur and tibia like in conventional method. 6 I am doing this study, as not many studies have been done on the radiological outcome or the effective component alignment using portable accelerometer-based hand held navigation system in TKA.…”
Section: Introductionmentioning
confidence: 99%